Quelques granges médiévales en Île-de-France et régions voisines - Jean-Yves Dufour; Claude de Mecquenem (Revue Archéologique du Centre de la France)
The archaeological observations made on nineteen barns over the last fifteen years, remind us the issues linked to these emblematic buildings of the cereal economy of the Paris Basin. Published in two parts, the article assesses the state of research on the subject of medieval and modern barn in a large Île-de-France area. Part I recalls descriptive and functional data from modern and contemporary agronomy textbooks. Based on three examples, the article questions the poor recognition of these buildings among the post planted buildings of the Middle Ages. The stone seigniorial barns of the late Middle Ages are better known. The transition from basilica-type barns with an opening on a gable wall, to peasant barn with opening on a drop wall remains to be clarified during the 15th and 16th centuries.The second part of this article will deal with barns of the modern period.The modern barns observed in elevation raise the question of the presence/absence of the buttresses, and therefore their usefulness. Other building principles can supplement them. The model of religious buildings is recalled, as well as the possible exchange of functions, between barn and religious building. The evolution of barn doors is symptomatic of the increase in yields in the modern and contemporary periods. The results of paleoecological analyzes of barn floors and threshing floor are given. The use of barns by cattle is attested on several sites. It is increasing with the development of agro-industrial activities in barns.